The Impact of Islamic Religious Learning and Social Media Distraction on Procrastination Behavior in Higher Education : Does the Screen Time Mediation Matter? - Pratiwi, Novia Eka; Heriyudanta, Muhammad; Daryono, Rihab Wit (Jurnal Paedagogy, 2024)
This study aims to investigate the influence of social media distraction and Islamic learning on academic procrastination behavior as well as the mediating role of screen time in these two variables. The research used a quantitative approach with a survey method, involving 97 students at MTs Muhammadiyah 3 Yanggong, located in Ponorogo Regency, East Java Province, as participants. The data collection technique was carried out using a Likert scale. Data analysis was carried out using the PLS-SEM technique to test the validity, reliability, and goodness-of-fit of the model. The research results showed that social media distraction had a positive and significant influence on increasing academic procrastination, while Islamic learning has an insignificant influence. Screen time also mediated the relationship between social media distraction and academic procrastination. The implications of this research highlight the need for awareness about the negative impacts of social media use and the importance of a focused approach in developing moral values to reduce academic procrastination. Recommendations include strengthening the Islamic learning curriculum, which includes media literacy and digital ethics, as well as the active role of parents in controlling children’s screen time. By implementing these recommendations, it is hoped that we can improve the balance between the use of technology, learning moral values, and reducing academic procrastination among students.